Emotion Regulation and Children With Attention-Deficit/Hyperactivity Disorder: The Effect of Varying Phonological Working Memory Demands. Issue 6 (April 2021) - Tarle, Stephanie J.; Alderson, R. Matt; Arrington, Elaine F.; Roberts, Delanie K.
Objective: Findings from extant studies of the relationship between ADHD-related emotion regulation and working memory deficits have been equivocal, and their correlational designs preclude inferences about the functional relationship between working memory demands and emotion regulation. This study aimed to experimentally examine the functional relationship between varying working memory demands and ADHD-related emotion regulation deficits.Method: Overt emotion regulation behaviors were coded while children with and without ADHD completed experimental tasks that manipulated low and high working memory demands.Results: Compared with typically developing children, children with ADHD exhibited large-magnitude overall emotion expression deficits, disproportionately greater self-criticism during high working memory conditions, and disproportionately greater positive emotion expression during low working memory demand conditions.Conclusion: These findings suggest that working memory demands are functionally related to emotion regulation deficits exhibited by children with ADHD and may explicate variability of emotion regulation difficulties related to environmental demands.